Kajian Teknis Pemanfaatan Potret Udara Non-Metrik Format Kecil Pada Bidang Kehutanan - I Nengah Surati Jaya; Agung Budi Cahyono (Jurnal Manajemen Hutan Tropika, 2001)
This paper describes the feasibility of small format non-metric aerial photographs (SFNAP) for forestry purposes. The analysis covers evaluation of the stereoscopic vision quality and the use of SFNAP for estimating stand variables such as tree height, crown diameter, crown density and number of trees. The study found that the SFNAPs were feasible to be applied for forestry purposes. Although the marginal information such as fiducial mark and nivo that usually used for determining the principal point and tilt are not available in the SFNAP, the study found that the stereoscopic vision could be made quite easy, and the stand variables could be well measured. Also, even though the SFNAPs were printed using enlargement process (not contact printing), the produced photographs were quite sharp and have good contrast.